2002
DOI: 10.1074/jbc.m207913200
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Mediates the Calcium-dependent Inhibition of Adipocyte Differentiation in 3T3-L1 Cells

Abstract: Recent studies have revealed that the calciumdependent serine/threonine phosphatase calcineurin mediates the effects of intracellular calcium in many different cell types. In this study we investigated the role of calcineurin in the regulation of adipocyte differentiation. We found that the specific calcineurin inhibitors cyclosporin A and FK506 overcame the antiadipogenic effect of calcium ionophore on the differentiation of 3T3-L1 preadipocytes. This finding suggests that calcineurin is responsible for media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 50 publications
8
106
0
1
Order By: Relevance
“…Our principal finding is that PGF2a inhibits adipocyte differentiation via a Gaq Gprotein subunit and calcium-dependent signaling pathway involving the calcium/calmodulinregulated serine/threonine phosphatase calcineurin. This conclusion is consistent with previous reports that PGF2a can act via its specific Gq-coupled FP prostanoid receptor to activate calcineurin in a number of cell types [Horsley and Pavlath, 2003;Liang et al, 2004], as well as with our recent identification of calcineurin as a critical calcium-dependent negative regulator of adipocyte differentiation [Neal and Clipstone, 2002]. We presume that this pathway is likely to operate in vivo to influence adipocyte development under conditions where PGF2a levels are elevated, such as those that occur during chronic inflammatory conditions as a result of increased expression of cyclooxygenase-2.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our principal finding is that PGF2a inhibits adipocyte differentiation via a Gaq Gprotein subunit and calcium-dependent signaling pathway involving the calcium/calmodulinregulated serine/threonine phosphatase calcineurin. This conclusion is consistent with previous reports that PGF2a can act via its specific Gq-coupled FP prostanoid receptor to activate calcineurin in a number of cell types [Horsley and Pavlath, 2003;Liang et al, 2004], as well as with our recent identification of calcineurin as a critical calcium-dependent negative regulator of adipocyte differentiation [Neal and Clipstone, 2002]. We presume that this pathway is likely to operate in vivo to influence adipocyte development under conditions where PGF2a levels are elevated, such as those that occur during chronic inflammatory conditions as a result of increased expression of cyclooxygenase-2.…”
Section: Discussionsupporting
confidence: 93%
“…The pMSCV-GFP, pMSCV-H2K, pMSCVPPARg, pMSCV-VIVIT-GFP retroviral expression vectors were created as previously described [Neal and Clipstone, 2002]. pMSCV-GFP-RGS2 was generated by introducing the GFP-RGS2 fusion sequence from pEGFP-C1-mRGS2 [Reif and Cyster, 2000] into pMSCV-H2K.…”
Section: Retroviral Expression Constructs and Infection Of 3t3-l1 Prementioning
confidence: 99%
See 2 more Smart Citations
“…This may be explained partly by immunosuppressive therapy (10), in particular steroids (11). Inhibition of endogenous calcineurin activity with tacrolimus or cyclosporine A (CsA) may lead to enhanced adipogenesis, which may explain the metabolic disturbances that are associated with these drugs (12). Some studies have reported linear relationships between doses or blood trough concentrations of CsA and lipids (inverse relationship with HDL) (13,14), but the potential impact of calcineurin inhibitors on serum adiponectin is unknown.…”
mentioning
confidence: 99%